In vitro antioxidant properties of underutilized baccaurea angulata fruit - Ahmed, Idris Adewale; Mikail, Maryam Abimbola; Ibrahim, Muhammad; Hazali, Norazlanshah; Abdull Rasad, Mohammad Syaiful Bahari; Abdul Ghani, Radiah; Abdul Wahab, Ridhwan; Arief Ichwan, Solachuddin Jauhari; Adros Yahya, Mohammad Noor (International Institute of Chemical, Biological & Environmental Engineering (IICBEE), 2013)
Six different crude extracts were obtained from the skin, pulp and whole fruit freeze-dried samples of Baccaurea angulata, an underutilized tropical fruit from Borneo Island of Malaysia. The effect of solvents on; total phenolic contents, total flavonoid contents, total carotene contents, free radical scavenging activities, phosphatidylcholine peroxidation inhibition activities and qualitative–quantitative compositions of ascorbic acid, carnosic, catechin, cinnamic and myricetin using using ultra high performance liquid chromatography were determined using their respective assays. The results indicated that methanol extracts contain higher TPC, TFC and TCC than PBS extracts for the various fruits’ parts. Methanol extracts also showed remarkable antiradical activity. A strong correlation was also found between pulp and whole fruit. Overall, the variations in the UHPLC results among the various extracts were consistent with the results obtained for TPC, TFC, TCC, DPPH radical scavenging activity and lipid peroxidation inhibition activities of the various crude extracts, especially, methanol extracts.